2022
DOI: 10.3390/ijerph19074372
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Risk Behavior and Lifetime HIV Testing: The Role of Adverse Childhood Experiences

Abstract: Despite the success of HIV prevention drugs such as PrEP, HIV incident transmission rates remain a significant problem in the United States. A life-course perspective, including experiences of childhood adversity, may be useful in addressing the HIV epidemic. This paper used 2019 BRFSS data to elucidate the role that childhood adversity plays in the relationship between HIV risk and HIV testing. Participants (n = 58,258) completed self-report measures of HIV risk behaviors, HIV testing, and adverse childhood e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 65 publications
(69 reference statements)
3
3
0
Order By: Relevance
“…To further explore the potential reasons for these findings, we developed additional post hoc analyses to examine associations between ACEs and ever having had an HIV test or recent HIV-related risk behavior. We observed that ACEs were positively associated with behaviors that increase the risk of STIs, including HIV, and with ever having had an HIV test, consistent with prior studies showing positive associations between ACEs and STI/HIV risk behaviors and more frequent STI testing 3,7,9,10 . These results support the theory that the positive associations between ACEs and HPV vaccination could be partly attributable to people receiving HPV vaccination recommendations or incidental HPV vaccination from their health care providers when accessing HIV/STI prevention or treatment.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…To further explore the potential reasons for these findings, we developed additional post hoc analyses to examine associations between ACEs and ever having had an HIV test or recent HIV-related risk behavior. We observed that ACEs were positively associated with behaviors that increase the risk of STIs, including HIV, and with ever having had an HIV test, consistent with prior studies showing positive associations between ACEs and STI/HIV risk behaviors and more frequent STI testing 3,7,9,10 . These results support the theory that the positive associations between ACEs and HPV vaccination could be partly attributable to people receiving HPV vaccination recommendations or incidental HPV vaccination from their health care providers when accessing HIV/STI prevention or treatment.…”
Section: Discussionsupporting
confidence: 89%
“…[2][3][4][5] Adverse childhood experiences, including sexual, physical, and emotional abuse, and neglect and witnessing violence, have also been linked to HIV risk behavior and/or increased risk of sexually transmitted infections (STIs) in adulthood. [6][7][8][9][10] Furthermore, childhood sexual abuse has been linked to an increased risk of genital human papillomavirus (HPV) infection. 11,12 Human papillomavirus is the necessary causal agent in cervical cancer, and HPV infections are also linked to vaginal, anal, vulvar, penile, and oropharyngeal cancers.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the prevalence of ACEs among persons with HIV risk behaviours in this study was 87.0%. Similar to the findings of Dyer et al (Dyer et al, 2022), the most commonly reported types of ACEs were parental separation/divorce and verbal abuse among the high-risk population. VanderEnde and colleagues (VanderEnde et al, 2018) found a dose-response relationship that exposure to ACEs was significantly associated with some sexual risk-taking behaviours and those with 3+ ACEs had increased odds of infrequent condom use.…”
Section: Discussionsupporting
confidence: 86%
“…A British study (Clifton et al., 2016) found that, although HIV testing increased with increasing risk perception, most people who perceive themselves as at risk of HIV have not recently tested. It may be due to the high ACEs burden among HIV‐related risk behaviours populations (Bertolino et al., 2020; Dyer et al., 2022; VanderEnde et al., 2018), that HIV‐risk population with ACEs don't care about their health status and do not take active steps to protect themselves.…”
Section: Discussionmentioning
confidence: 99%